INTERDISCIPLINARITY APPROACHES IN CONTEXT OF COMPLEX INTRAORAL REHABILITATON TREATMENT AT YOUNG PACIENTS WITH SOCIAL ANXIETY.-PART 2 - DIAGNOSTIC AND TREATMENT - - Lucian Stefan Burlea; Laura Elisabeta Checherita; Norina Consuela Forna; Tudor Hamburda; Veronica Serban Pintiliciuc; Magda Calina Barlean; Liana Aminov; Ovidiu Stamatin (Romanian Society of Oral Rehabilitation, 2024)
The therapeutic management of cases with social anxiety in addition to young ages must have a well-developed protocol to achieve the subsequent acquisition of confidence and the possibility of continuity in a short period of time because it takes place over several sessions as well as adaptations during the checks as maintenance and reliability of the treatment plan.